MENUJU DAKWAH ISLAM IDEAL DALAM MASYARAKAT INDONESIA - Akhmad Mubadilah Efendi (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2019)
Islam in Indonesia has existed successfully for hundreds of years. The entry of Islam into the archipelago is one of the great services provided by the spreaders of Islamic teachings, namely wali songo to the Indonesian people. The acceptance of Islam and its teachings in the midst of Indonesian society is none other than the policies and wisdom of the bearers of these teachings in socializing and preaching Islam. The main method they chose in preaching Islam in the midst of Indonesian society - which they realized was very diverse - was to reveal the true face of Islam and appreciate, respect and not infrequently adopt cultural diversity that is owned by the community so that social harmony occurs between the da'wah preachers and even though not all people can accept the teachings of Islam that they bring. In this case, the da'wah interpreters - who have been role models of society - are expected to be able to convey the message of good and true preaching, and always be 'wise in responding to cultural diversity so that social harmony will be realized, the community is easy to accept the teachings of Islam, and will manifest tolerance religious people in this country